Correction of skeletal Class III in a growing male patient by reverse pull facemask - P Kapoor; O P Kharbanda (Wolters Kluwer Medknow Publications, 2011)
The following case report describes the management of a 6-year-old male patient in early mixed dentition with a mesial step molar relation, an anterior reverse overjet, and skeletal Class III due to a slightly deficient maxilla. The treatment plan included protraction of the maxilla by a reverse pull Petit type facemask for 10 months followed by 15 months of active retention by a Frankel III appliance.